Differential expression of basal microRNAs' patterns in human dental pulp stem cells. Issue 3 (5th December 2014) - Vasanthan, Punitha; Govindasamy, Vijayendran; Gnanasegaran, Nareshwaran; Kunasekaran, Wijenthiran; Musa, Sabri; Abu Kasim, Noor Hayaty
Abstract MicroRNAs (miRNAs) are small non‐coding RNAs that regulate translation of mRNA into protein and play a crucial role for almost all biological activities. However, the identification of miRNAs from mesenchymal stem cells (MSCs), especially from dental pulp, is poorly understood. In this study, dental pulp stem cells (DPSCs) were characterized in terms of their proliferation and differentiation capacity. Furthermore, 104 known mature miRNAs were profiled by using real‐time PCR. Notably, we observed 19 up‐regulated miRNAs and 29 significantly down‐regulated miRNAs in DPSCs in comparison with bone marrow MSCs (BM‐MSCs). The 19 up‐regulated miRNAs were subjected to ingenuity analysis, which were composed into 25 functional networks. We have chosen top 2 functional networks, which comprised 10 miRNA (hsa‐miR‐516a‐3p, hsa‐miR‐125b‐1‐3p, hsa‐miR‐221‐5p, hsa‐miR‐7, hsa‐miR‐584‐5p, hsa‐miR‐190a, hsa‐miR‐106a‐5p, hsa‐mir‐376a‐5p, hsa‐mir‐377‐5p and hsa‐let‐7f‐2‐3p). Prediction of target mRNAs and associated biological pathways regulated by each of this miRNA was carried out. We paid special attention to hsa‐miR‐516a‐3p and hsa‐miR‐7‐5p as these miRNAs were highly expressed upon validation with qRT‐PCR analysis. We further proceeded with loss‐of‐function analysis with these miRNAs and we observed that hsa‐miR‐516a‐3p knockdown induced a significant increase in the expression of WNT5A. Likewise, the knockdown of hsa‐miR‐7‐5p increased the expression of EGFR. Nevertheless, further validation revealed the role of WNT5A as an indirect target of hsa‐miR‐516a‐3p. These results provide new insights into the dynamic role of miRNA expression in DPSCs. In conclusion, using miRNA signatures in human as a prediction tool will enable us to elucidate the biological processes occurring in DPSCs.